2006
DOI: 10.1136/jnnp.2006.087908
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson's disease with camptocormia

Abstract: Background: Camptocormia is defined as an abnormal flexion of the trunk that appears when standing or walking and disappears in the supine position. The origin of the disorder is unknown, but it is usually attributed either to a primary or a secondary paravertebral muscle myopathy or a motor neurone disorder. Camptocormia is also observed in a minority of patients with parkinsonism. Objective: To characterise the clinical and electrophysiological features of camptocormia and parkinsonian symptoms in patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
115
2
15

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(139 citation statements)
references
References 46 publications
7
115
2
15
Order By: Relevance
“…Camptocormia is enhanced during standing and walking [17] and relieved in recumbent or supine position [18,19,20]. In quite a number of cases, camptocormia is associated with lower back pain [1,3,7,21,22,23,24] but in others it is painless [19]. Camptocormia may be associated with concomitant weakness of the gluteus maximus and hip and genuflexion [3].…”
Section: Clinical Presentationmentioning
confidence: 99%
See 2 more Smart Citations
“…Camptocormia is enhanced during standing and walking [17] and relieved in recumbent or supine position [18,19,20]. In quite a number of cases, camptocormia is associated with lower back pain [1,3,7,21,22,23,24] but in others it is painless [19]. Camptocormia may be associated with concomitant weakness of the gluteus maximus and hip and genuflexion [3].…”
Section: Clinical Presentationmentioning
confidence: 99%
“…The term camptocormia derives from the Greek words ‘kamptos’ (to bend) and ‘cormos’ (trunk) [3]. The abnormal posture leads to lumbar kyphosis and is increased or only visible when the patient stands up or walks [3,4]. Camptocormia is most frequently due to disorders of the striated muscles of the spinal column, due to central nervous system (CNS) disorders, or due to some rare conditions (table 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While they found the technique to be safe, with only patients receiving the highest doses reporting mild weakness of hip flexion, they also found no significant postural improvement. Bloch et al 6 have reported a case control study (8 patients in each arm) and found that patients with PD and camptocormia responded poorly to levodopa treatment and had levodopa-unresponsive axial symptoms.…”
Section: Camptocormiamentioning
confidence: 99%
“…2,20,33 It is unclear if the prevalence of camptocormia varies with the severity of the PD. 3,6,11,20,33 Medical management of camptocormia in PD remains suboptimal. Azher and Jankovic 3 have reviewed the cases of 16 patients with camptocormia associated with PD (11 patients), dystonia (4 patients), and Tourette syndrome (1 patient).…”
Section: Camptocormiamentioning
confidence: 99%